Erectile Dysfunction Treatment Using Stem Cell Delivery Patch in a Cavernous Nerve Injury Rat Model - Moon, Hyong Woo; Kim, In Gul; Kim, Mee Young; Jung, Ae Ryang; Park, Kwideok; Lee, Ji Youl (MDPI AG, 2023)
Erectile dysfunction (ED) is a common and feared complication of radical prostatectomy (RP) for prostate cancer. Recently, tissue engineering for post-prostatectomy ED has been attempted in which controlled interactions between cells, growth factors, and the extracellular matrix (ECM) are important for the structural integrity if nerve regeneration. In this study, we evaluated the effects of a biomechanical ECM patch on the morphology and behavior of human bone marrow-derived mesenchymal stem cells (hBMSCs) in a bilateral cavernous nerve injury (BCNI) rat model. The ECM patch, made of decellularized human fibroblast-derived ECM (hFDM) and a biocompatible polyvinyl alcohol (PVA) hydrogel, was tested with human bone marrow-derived mesenchymal stem cells (hBMSCs) on a bilateral cavernous nerve injury (BCNI) rat model. In vitro analysis showed that the hFDM/PVA + hBMSCs patches significantly increased neural development markers. In vivo experiments demonstrated that the rats treated with the hFDM/PVA patch had higher ICP/MAP ratios, higher ratios of smooth muscle to collagen, increased nNOS content, higher levels of eNOS protein expression, and higher cGMP levels compared to the BCNI group. These results indicate that the hFDM/PVA patch is effective in promoting angiogenesis, smooth muscle regeneration, and nitrergic nerve regeneration, which could contribute to improved erectile function in post-prostatectomy ED.